RANCANG BANGUN SISTEM PENAMPILAN DINAMIKA TITIK PANAS DI INDONESIA BERBASIS KEYHOLE MARKUP LANGUAGE (KML) DINAMIS - Budhi Gustiandi (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2011)
Hot spot dynamics display system based on Dynamic Keyhole Markup Language (KML) have been designed and built in Indonesia as a complement of web-based Indonesian fire watch system that have been developed by Indofire. Indofire’s system uses web browsers to display it’s output data, while the built system uses earth/geo browser to display data. The results show that the built system has feature that more user friendly, data access speed up to 5.22 times faster, and reducing data volume storage need up to 80.87 % rather than system that has been developed by Indofire.Keywords: Keyhole Markup Language (KML), Earth/geo browser, Hot spot monitoring system.